MULTI-CRITERIA OPTIMIZATION OF SPECIAL-PURPOSE GEODETIC NETWORK USING THE VIKOR METHOD - Tamara Kecojević; Filip Mileski (Geodetski Glasnik)
This paper discusses and applies an approach for the design of a geodetic network intended to serve as an adequate basis for analyzing the verticality of buildings in Podgorica, Montenegro. The method analyzed in this paper is the Multi-Criteria Compromise Ranking/Solution (VIKOR), a technique used in multi-criteria optimization for different systems. During the research preparation, six competitive alternatives were established. The ranking of these alternatives was carried out based on four different preference approaches. The primary difference between these approaches lies in the varying weights assigned to certain criteria. Specifically, the weight ratios for individual criteria were adjusted. For the analysis of the building's verticality, a geodetic network design, selected as the optimal compromise solution, was utilized. The network measurements were conducted using appropriate geodetic instrument and supporting equipment. After completing the measurements in the optimized network, the network was adjusted, and the accuracy of the positional coordinates was assessed.